Timing grace in lockdown liturgies. : South African and Dutch responses compared - Wepener, Cas; Cilliers, Johan (Stellenbosch Theological Journal, 2022)
The similarities and differences regarding responses in the media to the phenomenon of lockdown liturgy in the Netherlands and South Africa is firstly explored in this article. The findings of Goyvaerts and Woude, which is based on their study of discussions in Dutch media, is briefly presented and thereafter compared to responses in the South African Afrikaans media. Based on this comparison, core themes are identified and discussed as creative liturgical theological tensions pertaining to lockdown liturgies. These tensions include: Excarnation – Incarnation; Global – Local; and Prophetic – Pastoral. Revisiting and exploring these tensions are invaluable for reimagining the liturgia condenda pertaining to lockdown liturgy specifically and online liturgy in general.